Penerapan Total Productive Maintenance Guna Mengoptimalkan Ketersediaan Mesin di PT. ATMI Solo - Darsini, Darsini; Aditya Prabantara, Yonatan (Journal of Applied Mechanical Engineering and Renewable Energy, 2024)
Optimal productivity needs to be supported by the availability of machines that are always ready to produce. The condition that needs to be maintained is that the machine does not stop frequently due to damage and causes the continuity of production to be hampered. According to the Japan Institute of Plant Maintenance (JIPM), the level of machine availability (availability) is said to be ideal when it exceeds 90%. At PT. ATMI Solo, 23.8% of 21 CNC machines still have availability percentage below 90%, namely Salvagnini S4 punching machine (69%), Starrag CF100 milling machine (79%), Trubend 3180 bending machine (82%), milling machine YCM TV 158B (82%), and Trumatic TC 200 R punching machine (89%).The main factor is the low availability of machines at PT. ATMI Solo is high machine downtime due to a breakdown. Therefore, it is necessary to implement Total Productive Maintenance (TPM) to optimize the availability of these machines. The implementation of TPM is Training and Education, Autonomous Maintenance, Planned Maintenance, and TPM in Administration (TPM in Administration), especially in the spare part Logistics section. The implementation of the TPM succeeded in increasing the availability percentage above 90% (based on data from the 2022 General Maintenance Daily Report), namely the Salvagnini S4 punching machine (94.13%), Starrag CF100 milling machine (96.36%), Trubend 3180 bending machine (99, 70%), YCM TV 158B milling machine (99.97%), and Trumatic TC 200 R punching machine (99.88%).